Individual and regional determinants of long-term care expenditure in Japan: evidence from national long-term care claims - Jin, Xueying (Eur J Public Health, 2020)
BACKGROUND: Japan, with the oldest population in the world, faces a financial challenge caused by rising long-term care (LTC) expenditure. For policymakers to address this, it is important that we have a better understanding of how individual and regional characteristics affect LTC expenditure. METHODS: We linked national LTC insurance (LTCI) claim data, covering the entire population who used LTCI services in Japan, with municipality data on an individual level. Individuals 65 years and older (n=3 876 068) who had used LTCI benefits at least once in the fiscal year (FY) 2016 were included. We examined the associations of individual and municipality characteristics regarding supply and demand of healthcare with the LTC expenditures on facility care, home and community care, and total care (the sum of both types of care), after adjusting for regional differences in LTC extra charges. RESULTS: The following variables were associated with higher total expenditure; at the individual level: female, a higher care-need level, a lower income (0% co-payments) or a facility service user; at the municipality level: municipalities locating in metropolitan areas, with a higher proportion of single elderly households, more doctors per 1000 citizens, more nursing homes per 100 000 LTC benefit users or more outpatient medical spending per citizen ≥75 years old. CONCLUSIONS: As we are able to identify several individual and municipality characteristics associated with higher LTC expenditure in Japan, the study offers insights into dealing with the rapidly growing LTC expenditure.